Gravitational Model of Compact Spherical Reissner-Nordström-Type Star Under f(R, T) Gravity. Issue 1 (2nd January 2021) - Islam, Safiqul; Kumar, Praveen
Abstract: We present the interior solutions of distributions of charged fluid inside a sphere in f ( R, T ) gravity and which admits the existence of conformal Killing vectors. The charged sphere is embedded in an exterior RN metric. We assume that all physical quantities axe in static equilibrium. The perfect fluid matter is studied under a particular form of the Lagrangian density f ( R, T ), and smooth matching conditions with the exterior RN metric are applied. The energy conditions as well as the stability of the solutions are also investigated. Emission from the surface of such a star is shown to blueshifted, rather than redshifted, and we calculate its value. Furthermore, the fluid body under f ( R, T ) gravity is shown to be non-geodesic in nature.